Immunoglobulin sub-class distribution in bipolar disorder and schizophrenia: potential relationship with latent Toxoplasma Gondii infection - Hamdani, Nora; Bengoufa, Djaouida; Godin, Ophélia; Doukhan, Raphaël; Le Guen, Emmanuel; Daban-Huard, Claire; Bennabi, Meriem; Delavest, Marine; Lépine, Jean-Pierre; Boukouaci, Wahid; Laouamri, Hakim; Houenou, Josselin; et al. (BMC psychiatry, 2018)
Background Immune dysfunction could play a significant role in the pathogenesis of bipolar disorder (BD) and schizophrenia (SZ), conditions with an underlying pro-inflammatory state. Studies on humoral immune responses (which reflects antibody mediated fight against pathogens) in schizophrenia and bipolar disorder are sparse and often providing contradictory results. The aim of this study was to assess humoral immunity in a group of stable bipolar disorder and schizophrenia patients compared to controls by determining total Immunoglobulins and IgG subclasses and to assess their association with latent Toxoplasma gondii and/or CMV infection. Methods 334 subjects (124 BD, 75 SZ and 135 Healthy Controls [HC]) were included and tested for humoral immunity by determining the total immunoglobulins (IgG,A and M) and IgG subclasses (IgG1, IgG2, IgG3, IgG4) and their relationship with latent Toxoplasma gondii infection, an established risk factor for BD and SZ. Results Although lower levels of IgG, IgG1, IgG2, IgG4 and IgA were found among BD as compared to HC and/or SZ, after adjustment for confounding variables, only low levels of IgG and IgG1 in BD remai- ned significant. Strikingly highest levels of antibodies to T. gondii (but not CMV) infection in BD and SZ were associated with lowest levels of IgG3 and IgG4 levels as compared to controls. Conclusions Schizophrenia and bipolar disorder patients with latent T. gondii specific infection may be more vulnerable to changes in immuno-inflammatory processes than controls with similar latent infectious state. Simultaneous sequential immunological monitoring both in steady state and active disease phases in the same BD and SZ patients are warranted to understand the role of Toxoplasma gondii latency in these disorders.